Methodical of forming self-control in students of grades 5-6 when studying numbers - Bondareva I. A., Smykovskaia T. K. (The Topical Issues of the Humanities and Social Sciences: from Theory to Practice, 2023)
The article presents an overview of methodological approaches to the formation of self-control among students of grades 5-6 in the study of mathematics. The analysis of the state of this issue showed that in the works of A.A. Krylov, S.D. Yakushev and G.K. Selevko, etc., the importance of self-control within the framework of organizing independent work in the classroom and in the works of A.G. Mordkovich, Yu.M. Kolyagin, etc. in general, when studying mathematics on the example of a numerical line is indicated. It is proved that one of the means of forming self-control among students of grades 5-6 are assessment sheets, which include the objectives of studying the subject content, a route sheet for the lesson with the stages of academic work, a system of reflexive assessments.
Keywords: самостоятельная работа; самоконтроль; обучение математике; teaching mathematics; self-control; independent work; оценочный лист; содержательно-методическая линия; методика изучения чисел; assessment sheet; content-methodical line; methods of studying numbers